The “sick imagination” of Godwin’s Fleetwood - Melville, Peter (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2014)
This essay contends that Fleetwood; or the New Man of Feeling is similar to Godwin’s first two major novels Caleb Williams and St. Leon inasmuch as it is a narrative of emerging self-consciousness. Fleetwood recounts a tale throughout which he struggles to understand the core of his own misanthropy. Unlike Caleb Williams and Reginald de St. Leon, however, Fleetwood does not gain self-awareness by turning to and identifying with forms of otherness. Rather, it comes on the heels of a long and tragic history of turning from the other in whose face Fleetwood persistently witnesses the distorted reflections of his own depravity and self-disgust. This essay considers Fleetwood’s various turns from other to self and questions whether his final retreat into writing facilitates or forecloses a reciprocal engagement with the other, including his wife Mary who returns in the novel’s conclusion to offer forgiveness for his deplorable treatment of her.